Survey of ICT and Education in Africa : Uganda Country Report - Farrell, Glen (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. As it adopts ICT in education, Uganda faces the same challenges as most developing economies - poorly developed ICT infrastructure, high bandwidth costs, an unreliable supply of electricity, and a general lack of resources to meet a broad spectrum of needs. However, with the rapid emergence of wireless network capacity and the ubiquitous growth of mobile phones, the context of the infrastructure is changing. A national ICT policy is in place and an education sector ICT policy is before cabinet. The ministry of education and sports is taking steps to co-ordinate ICT development and has allocated resources to support implementation of its ICT strategy.